Analysis Of The Influence Of Location, Design, Product Quality On The Decision To Purchase Subsidy Housing In Madiun Regency - Dian Citaningtyas Ari Kadi; Rizal Ula Ananta Fauzi; Andrea Ageany (Cita Konsultindo Research Center, 2022)
This research is entitled Analysis of the Effect of Location, Design, Product Quality on Decisions to Purchase Subsidized Housing in Madiun Regency. to determine the effect of product quality location on the decision to purchase subsidized housing in Madiun district and to determine the effect of location location, design and product quality simultaneously affect the decision to purchase subsidized housing in Madiun district. This type of research is quantitative research. The number of samples used is 291 respondents. The sampling technique used is non-probability sampling, with purposive sampling method. Data retrieval using a questionnaire with the distribution via google form. The results show that a) location (X1) has a significant effect on purchasing decisions (Y), b) design (X2) has a significant effect on purchasing decisions (Y), c) quality (X3) has a significant effect on purchasing decisions (Y), d) location (X1), Design (X2), quality (X3) simultaneously have a significant effect on purchasing decisions (Y)